Challenges of liberalization and democratization in Georgia: The case of the modern civic calendar of the country - Ivane Tsereteli (CES Working Papers, 2017)
The case of Georgia's transformation through the analysis of a civic calendar demonstrates existing problems on the way of country's democratization. Its design in terms of national festivities and celebrations contradicts the declared course of the Georgian state, which is aimed at building an inclusive civic Georgian nation, as it is cantered only at the Orthodox population of the country. The multi-ethnicity of the Georgian nation – the political and cultural role of national minorities in the Georgian state – is not reflected in the civic calendar of the state. Considering the popularity of the Georgian Orthodox Church among the Georgian society and its influence on the formation of public opinion, a range of challenges could emerge on Georgia's way towards democratization, as some aspects of the liberal ideology is termed as dangerous for the Georgian culture by the Georgian Orthodox Church.
Keywords: 330; Georgia; calendar; democratization; transformation